THE RELATIONSHIP BETWEEN THE IMPLEMENTATION OF SCHOOL SUPERVISORS' SUPERVISION, THE SCHOOL PRINCIPLE'S LEADERSHIP STYLE AND MOTIVATION ON TEACHER PERFORMANCE - NURYATI, Nuryati; NURAINI, Betti; AL-JUFRI, Hamid (Journal of Education and Leadership in Education, 2023)
The purpose of this study is to investigate The relationship between the implementation of school superintendent's supervision, the transformational leadership style of the principal and the motivation together for teacher performance. The research approach used in this study is a quantitative approach. The population in this study was all elementary school teachers in Cluster 3, Karang Tengah District, Tangerang City with a sample of 144 teachers who were taken randomly (random sampling). The analysis technique used is a double correlation analysis technique. Based on the results of the analysis, it is known that: 1) There is a positive and significant relationship of supervisory supervision with teacher performance. 2) There is a positive and significant relationship of leadership with teacher performance, 3) There is a relationship between work motivation and teacher performance. 4) There is a positive and significant impact of supervisory supervision, traditional leadership and work motivation together with teacher performance. Level of relationship between supervisory supervision Traditional leadership and work motivation with Teacher performance in a very high relationship category